Alexander McKinstry, The Code of Ordinances of the City of Mobile, with the Charter, and an Appendix - (:unkn) unknown (My University, 1859)
118, § 124; Prohibited the discharge of any gun, pistol, fowling-piece, or fire-arm.
Keywords: DISCHARGE